Perbedaan respon Aedes aegypti (Linnaeus) (Diptera: Culicidae), terhadap paparan anti nyamuk bakar dan bunga keluwih (Artocarpus camansi, Blanco) - Nur Endah Wahyuningsih; Ramauli Agustina Sihit (Jurnal Entomologi Indonesia, 2015)
The control of dengue hemorrhagic fever (DHF) it is important to control the vector, i.e. Aedes aegypti (Linnaeus) and Ae. albopictus (Skuse). Usually, controls of these vectors are done using chemical insecticides. Research on mosquito resistance has been done, but the impact of mosquitoes that survive after synthetic (chemical) insecticides application has not been studied. The aim of this research was to analyze the differences of fecundity, fertility and vitality rate of mosquitoes that were exposed to natural insecticides i.e with burned breadnut flowers and mosquito coils containing transflutrin and d-aletrin. Mosquito samples were taken from field eggs which were exposed with synthetic and natural insecticides. Mosquitoes that remainder alive after 24 hours exposure were mated and each group were put in 2 cages, each repetition were repeated 3 times. The mosquito eggs were observed until adult mosquitoes die. Then, the fecundity, fertility and vitality rate were compared. Based on our analysis, there were no differences on fecundity rate, between control and mosquitoes that were exposed to natural insecticides, but there were significant differences between the control and the synthetic insecticides. Natural insecticides do not increase the rate of fecundity but synthetic insecticides may increase the rate of fecundity and number of mosquitoes and causes the mosquito lifespan longer than the control and natural insecticide treatment.